Agostinho de Hipona : o mal e sua relação com a vontade humana - Gomes, Izaias dos Santos Goes (2018)
This study aims to analyze the relationship between thehuman will with the problem of evil from the of Augustine thought. Since your youth Augustine questioned about the problem of evil and saw in the Manichean dualism a reasonable response as a solution to the problem. After nearly a decade in Manichaeism, Aurelio Augustine moved to Rome and then Milan, where he participated in Platonic studies group. However, the contact of Augustine, in Milan, with the Catholic Bishop Ambrose led him to conversion to Catholicism and the abandonment of Manichaeism. From this, Augustine prepared your theory about evil, that relate directly to human will. In this perspective, evil is not a being, as he taught the Manichaeism, but as a result of the free will of the human being by your will stop wanting want God as supreme good for wanting a well more than himself. In this way, the desire human being deprived of God, corrupting the relationship between the divine and the human.